proszę potrzebne mi na teraz
(3x – 5y) – (2x -9y +3)=




5b( 2 – 4b) + 4( 2a -3b)=




3 (k – 2r) + (3r -6k) :2=




(2 x – 4y + 6 z) ·5 – 3(x + 4y – 5z) =



Odpowiedź :

Odpowiedź:

(3x – 5y) – (2x -9y +3)= x + 4 y - 3

5b( 2 – 4b) + 4( 2a -3b)=2 (4 a - 10 b^2 - b)

3 (k – 2r) + (3r -6k) :2=1/2 (3 (k - 2 r) - 6 k + 3 r)

(2 x – 4y + 6 z) ·5 – 3(x + 4y – 5z) =7 x - 32 y + 45 z

(3x – 5y) – (2x -9y +3)= 3x- 5y - 2x + 9y - 3 = x +4y - 3

5b( 2 – 4b) + 4( 2a -3b)= 10b - 20b^2+ 8a - 12b = -2b - 20b^2 + 8a

3 (k – 2r) + (3r -6k) :2= 3k - 6r + 3r-6k/2 = 6k - 12r + 3r - 6k/2 = -9r/2

(2 x – 4y + 6 z) ·5 – 3(x + 4y – 5z) = 10x - 20y +30z - 3x - 12y +15z = 7x - 32y +45z